PENGARUH WORKING CAPITAL TURNOVER, RECEIVABLE TURNOVER DAN FIRM SIZE TERHADAP PROFITABILITAS DIMODERASI LIKUIDITAS PADA PT. “LK” SEMARANG PERIODE 2013-2016 - Patricia Dhiana Paramita (Jurnal Ekonomi dan Bisnis Kontemporer, 2018)
In principle, the profitability of a company is affected by working capital turnover, receivable turnover and firm size. The analysis of working capital turnover, receivable turnover and firm size for each company is very important to do to determine the current financial condition of the company and the financial situation in the future. This study aims to determine the effect of working capital turnover, receivable turnover and firm size partially to profitability moderated by liquidity.Sources of data used are secondary data, which is related to the object of research, namely PT. "LK" Semarang, a company engaged in furniture, in the form of financial data from 2013 to 2016. Analytical techniques used are multiple linear regression with MRA, classical assumption test and goodness of fit test.The calculation results show that the working capital turnover, receivable turnover and firm size partially have a positive and significant impact on profitability. In addition, liquidity strengthens the influence of working capital turnover on profitability, liquidity weakens the influence of receivable turnover on profitability, and liquidity also weakens firm size influence on profitability. The policy that needs to be done by management is to improve the management of working capital turnover receivable turnover and firm size, in order to improve the profitability of the company.Keywords: working capital turnover, receivable turnover, firm size, profitability, and liquidity